La presenza della Bibbia nell'opera di Bonvesin da la Riva - Colombo, Michele (Verbum – Analecta Neolatina, 2015)
The paper offers a brief survey of the ways in which Bonvesin da la Riva, the most important Milanese poet in the Middle Ages, embodies biblical references in his poetical work.